PEMBELAJARAN MENULIS CERITA PENDEK PADA SISWA KELAS X DI MA AL-FATAH - Yanti Jelita; Ni Nyoman Wetty Suliani; Mulyanto Widodo (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem presented in this research is about a learning process of writing short stories of X class’ students at MA Al-Fatah Natar Lampung Selatan Academic Year 2012/2013. Based on those issues this research aims to describe the learning process that includes planning, implementation, and evaluation of learning to write short stories based on self-experience. The method used in this research is descriptive method. resources of this research is the activities of learning to write short stories in class X MA Al-Fatah Natar Lampung Selatan there will be observation activities on planning of the learning process, and evaluation of the learning. the techniques that is used in data collection of this research is observation of the teacher and students.data analysis techniques that are used in this research is the analysis of data flow models, which refers to the theory of Miles and Huberman which consist of three activities, they are data reduction, data display, and conclusion. The learning process of the short story writing of class X MA Al-Fatah are focused on: the planing of learning, implementation activities of writing, the teacher will use writing test techniques Kata kunci: evaluasi, pelaksanaan, perencanaan pembelajaran